Epistolary dialogues between Jorge de Sena and João Gaspar Simões - Martins, José Cândido de Oliveira (2022)
The letters exchanged between Jorge de Sena and João Gaspar Simões, between 1943 and 1977, are quite rich in several aspects, despite their scarcity. Their existences as writers and literary critics have some points of rapprochement. However, it is much more the differences that separate them. All this explains the estrangement that happened between the two intellectuals, overcome by a final reunion. What is important is the balance of this correspondence, materialized in the broad documental interest, in cultural and literary terms.